Ibn Fadlan and the land of darkness : Arab travallers in the far North - Ibn Fadlan, Ahmad, active 922.; Lunde, Paul, 1943-; Stone, Caroline (England : Penguins Classics, 2012)
'In 922 AD, an Arab envoy from Baghdad named Ibn Fadlan encountered a party of Viking traders on the upper reaches of the Volga River. In his subsequent report on his mission he gave a meticulous and astonishingly objective description of Viking customs, dress, table manners, religion and sexual practices, as well as the only eyewitness account ever written of a Viking ship cremation. Between the ninth and fourteenth centuries, Arab travellers such as Ibn Fadlan journeyed widely and frequently into the far north, crossing territories that now include Russia, Uzbekistan and Kazakhstan. Their fascinating accounts describe how the numerous tribes and peoples they encountered traded furs, paid tribute and waged wars. This accessible new translation offers an illuminating insight into the world of the Arab geographers, and the medieval lands of the far north.'--Publisher's website
The book of Ahmad ibn Fadlan, 921-922 -- The travels of Abu Hamid al-Andalusi al-Gharnati, 1130-1155 -- Passages from other geographers, historians and travellers.
Includes bibliographical references (pages 214-221)
Translated from the Arabic into English; glossary in Arabic with English translations.
Sumbangan Mohamad Taha (2017).
Keywords: Ibn Fadlan, Ahmad, -- active 922 -- Travel -- Russia (Federation) -- Volga River Region; Ibn Fadlan, Ahmad, -- active 922 -- Travel -- Asia, Central; Bulgars (Turkic people) -- Russia (Federation) -- Volga River Region -- History; Tatarstan (Russia) -- Description and travel -- Early works to 1800.; Volga River Region (Russia) -- Description and travel -- Early works to 1800.; Asia, Central -- Description and travel -- Early works to 1800.